2022
DOI: 10.1186/s12859-022-04674-2
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of topologically associating domain callers over mammals at high resolution

Abstract: Background Topologically associating domains (TADs) are locally highly-interacting genome regions, which also play a critical role in regulating gene expression in the cell. TADs have been first identified while investigating the 3D genome structure over High-throughput Chromosome Conformation Capture (Hi-C) interaction dataset. Substantial degree of efforts have been devoted to develop techniques for inferring TADs from Hi-C interaction dataset. Many TAD-calling methods have been developed whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 109 publications
2
20
0
Order By: Relevance
“…We observed that TAD assignments are very sensitive to many parameters, among which include resolution of bins and size of the moving window, which has been seen by us and others, and remains a key area in bioinformatic research ( 59 , 60 ). For our analysis, we used 50 kb bins and a moving window of 10-fold on each side, resulting in median TAD size of ∼1 Mb (Figure 2A and B).…”
Section: Resultsmentioning
confidence: 51%
“…We observed that TAD assignments are very sensitive to many parameters, among which include resolution of bins and size of the moving window, which has been seen by us and others, and remains a key area in bioinformatic research ( 59 , 60 ). For our analysis, we used 50 kb bins and a moving window of 10-fold on each side, resulting in median TAD size of ∼1 Mb (Figure 2A and B).…”
Section: Resultsmentioning
confidence: 51%
“…The inferred results of different TAD identification methods are also different. The resolution size is another factor that affects the results [120] . Current criteria for evaluating TAD identification tools include robustness concerning bin size and normalization strategy, the minimum required data volume, reproducibility, biological relevance, and computational efficiency [121] .…”
Section: Discussionmentioning
confidence: 99%
“…They are introduced in Zufferey et al [2018], Liu et al [2022] and Sefer [2022]. Since the bin size in our experiments is 10kb, we adjust the definitions of these three metrics as the following:…”
Section: H4 Chip-seq Peak Calling and Analysis On Graphsmentioning
confidence: 99%